Konsep Diri dan Masalah yang Dialami Orang Terinfeksi HIV/Aids - Wahyu, Surahma; Taufik, Taufik; Ilyas, Asmidir (Konselor, 2012)
Abstrak this research early from fact that growing of patient of HIV aids specially in West Sumatra. Natural Patient of dread, stress, depresi, soul convulsion, and discrimination of stigmatisasi. Here in after the situation will pursue development of self concept of odha positively causing low feeling of self, feel worthless self and show wrong behaviour. This research is descriptive research with aim to express self concept and natural by dominant problems of odha.